Ácido docosahexaenoico (DHA) y el resveratrol en el manejo de la angiogénesis a nivel ocular: Revisión bibliográfica (2020)
Natural antioxidants such as resveratrol and docosahexaenoic acid (DHA) have been studied for their potential properties in different eye conditions, this has led to the identification of the implementation of resveratrol and DHA in the improvement of retinal pigment epithelium storage in adults, light-induced retinal degeneration, attenuation of the inflammatory retinal condition and damage from diabetic retinopathy. The objective of this bibliographic review is to describe the existing evidence of the use of DHA and resveratrol in the management of angiogenesis at the eye level through a bibliographic review, through a review of documents from the last 20 years of scientific societies dedicated to visual health, indexed in the databases, demonstrating the importance and benefits that dha and resveratrol use brings in the management and improvement of eye angiogenesis and its studies on the subject, concluding that they are natural alternatives that contribute to a stoppage or delay in the progression of retinal degenerative diseases, which should be studied more deeply for an expansion of information for greater clinical utility.